1982
DOI: 10.1038/299824a0
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroouabain is an antagonist of ouabain inotropic action

Abstract: The Na+, K+-pump controls a wide variety of cellular systems and its inhibition by cardiac glycosides modifies important physiological functions and evokes several pharmacological effects (refs 1, 2 and refs therein). However, not all the actions of cardiac glycosides can be attributed to Na+, K+-pump inhibition and several observations show that, at low doses, cardiac glycosides stimulate the pump. It has been proposed that their positive inotropic effect could be the sum of two processes: the inhibition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In this preparation, Na+, K+-pump inhibition seems to be the only mechanism responsible for the positive inotropic effect of dihydroouabain, the derivative of ouabain with a saturated lactone ring (Godfraind & Ghysel-Burton, 1980). Furthermore, dihydroouabain has been shown to act as an antagonist to the positive inotropic effect of ouabain that is independent of Na+, K+-pump inhibition (Godfraind, Ghysel-Burton & De Pover, 1982). Therefore, we have studied the inotropic action of dihydroouabain on rat ventricular strips and examined how this drug interfered with the action of ouabain.…”
Section: Introductionmentioning
confidence: 85%
“…In this preparation, Na+, K+-pump inhibition seems to be the only mechanism responsible for the positive inotropic effect of dihydroouabain, the derivative of ouabain with a saturated lactone ring (Godfraind & Ghysel-Burton, 1980). Furthermore, dihydroouabain has been shown to act as an antagonist to the positive inotropic effect of ouabain that is independent of Na+, K+-pump inhibition (Godfraind, Ghysel-Burton & De Pover, 1982). Therefore, we have studied the inotropic action of dihydroouabain on rat ventricular strips and examined how this drug interfered with the action of ouabain.…”
Section: Introductionmentioning
confidence: 85%
“…Does the existence of two dasses of cardiac glycoside receptors represent the exception, being restricted to the rat , or does it represent a more common phenomenon? At least for some species (guinea pig , dog, man) , experimental evidence is present for different receplor types [36][37][38][39][40].…”
Section: Comparison 0/ Cardiac Glycoside Receptors In Rat Und Chickenmentioning
confidence: 99%
“…In the guinea-pig isolated atria, it has been observed that amiloride inhibits the positive inotropic effect of both ouabain and dihydroouabain, whereas EIPA inhibits the effect of ouabain but not that of dihydroouabain (Ghysel-Burton & Godfraind, 1986). In guinea-pig atria, the inotropic effect of dihydroouabain has been attributed to an interaction with low affinity binding sites, whereas the inotropic effect of ouabain has been ascribed to an interaction with both low and high affinity binding sites (Godfraind et al, 1982). In the present experiments, we have studied the action ofEIPA on the inotropic effect ofouabain in rat ventricular strips where two different Na/K-ATPase activities with different affinities for ouabain have 'Author for correspondence.…”
Section: Introductionmentioning
confidence: 96%
“…In guinea-pig atria, the inotropic effect of dihydroouabain has been attributed to an interaction with low affinity binding sites, whereas the inotropic effect of ouabain has been ascribed to an interaction with both low and high affinity binding sites (Godfraind et al, 1982).…”
Section: Introductionmentioning
confidence: 99%